Principles of Islamic literature in the poems of Ma'moun Jarrar - Bahman Mirzazadeh; Abdolhamid Ahmadi; Foad Abdolahzadeh (دراسات فی اللغه العربیه و آدابها, 2021)
Islamism in the literature is an independent school that followed the publication of Western literary schools in Islamic countries. In this school the poet looks at the universe and humanbeings from the Islamic point of view. He believes that the only alternative way of solving all social and individual crises is found in following the Islamic teachings. Ma'moun Jarrar (1949), the Palestinian poet, received the effectiveness of such approach to create his own poems. For The importance of this stream in the literary field, this study tries and is based on the descriptive-analytical approach to review the Islamic trends in the poetry of Mamoun Jarrar. The poet’s reliance on “Islamic” principles in his treatment of various social and political issues is one of the most important characteristics of his poetry. His review of the Palestinian issue with a religious connotation, the lament of the entire Islamic nation, the desire to adhere to the Islamic teachings to revive the religious culture, and his extensive use of Quranic intertextuality and prophetic hadith in all its poetic contents, all this clearly indicates the extent of the poet’s commitment to Islamic principles in his poetry.